Method for symmetrization and estimation of solutions of the Neumann problem for the equation of a porous medium in domains with noncompact boundary for infinitely increasing time - Bazalii, B. V.; Tedeev, A. F. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We consider the initial boundary-value Neumann problem for the equation of a porous medium in a domain with noncompact boundary. By using a symmetrization method, we obtain exactL p-estimates, 1≤p≤∞, for solutions as t→∞.